Effects Of Methyl Metsulphuron Herbicide Against Periphyton Algae Community Structure - Kustia Dewa, Satria Dharmawan; Sucahyo, Sucahyo; Kasmiyati, Sri (Metamorfosa: Journal of Biological Sciences, 2020)
Agricultural activity can’t be separated from synthetic herbicide. Some synthetic herbicide use metsulfuron methyl as active ingredient that works to change chemical materials in weed’s tissues so able to exterminate the tissue or disordering physiological system that needed for survivability of weeds. Because of that effect a question arises whether this compound also can affect non target organisms like periphyton algae. Periphyton is a group of microscopic organisms that grows attached to surface of objects or water plants, not penetrate the substrate, staying or moving on the substrate surfaces. One of main compilers of periphyton community is algae. Periphyton algae in water has significant role to determining primary productivity and as bioindicator of water quality. Some research that has been done shows if some active ingredient in particular concentration significantly affects toward primary productivity of periphyton algae and able to inhibit growth of certain algae species. This research was conducted to find out effects of metsulfuron methyl herbicide on periphyton algae community structure. Parameters measured are concentration of chlorophyll a, density, richness, diversity, evenness, and domination indices also periphyton algae species identification.  Research conducted in laboratory scale use samples taken from Rawa Pening Lakes, Semarang District, Central Java. Observation time is 21 days with herbicide exposure at 0, 0.05, 0.1, 0.2, and 0.4 mg/L. Results show that periphyton algae community structure more impacted by exposure period of herbicide actve ingredient metsulphuron methyl than concentration that used in research. Keywords: Periphyton Algae, Metsulfuron Methyl, Community Structure